2022
DOI: 10.1021/acs.macromol.2c00447
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Micelles through a Nanochannel

Abstract: Flow-driven translocation of micelles self-assembled from amphiphilic diblock copolymers through a nanochannel is studied by using hybrid lattice-Boltzmann molecular dynamics simulations. It is discovered that the structure of the translocating micelles depends on their initial sizes. Intact translocation occurs for small micelles, whereas fragmented translocation takes place for large micelles. The fragmented micelles reassemble to form an intact micelle after translocation. Coexistence of these two transloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Our previous work has shown that the critical flow flux can be used to characterize the stability of the micelle by indicating the minimum flow flux that is just enough to allow the micelle to be disrupted and squeezed into a small nanochannel smaller than its size. 13 Thus, we calculate the translocation probability [ P ( J )] in Fig. 2, where (a)–(c) are the comb-like copolymer micelles and (d)–(f) are the corresponding diblock copolymer micelles, and the critical flow flux ( J c ) is defined as the flow flux when P ( J ) = 0.5, denoted by the auxiliary dashed lines.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous work has shown that the critical flow flux can be used to characterize the stability of the micelle by indicating the minimum flow flux that is just enough to allow the micelle to be disrupted and squeezed into a small nanochannel smaller than its size. 13 Thus, we calculate the translocation probability [ P ( J )] in Fig. 2, where (a)–(c) are the comb-like copolymer micelles and (d)–(f) are the corresponding diblock copolymer micelles, and the critical flow flux ( J c ) is defined as the flow flux when P ( J ) = 0.5, denoted by the auxiliary dashed lines.…”
Section: Resultsmentioning
confidence: 99%
“…11,12 In our previous work, we have demonstrated that the stability of micelles can be well characterized by their flow inside a nanochannel through the flow-driven translocation; that is, the translocation of micelles, including intact and fractured modes, is dependent on their initial size. 13…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for the former, as long as the drag force from the fluid is sufficiently high to overcome the confinement force imposed by the channel interface, the conformational transition and translocation event occur simultaneously. Such a topic has received much attention in the previous theoretical and experimental studies. …”
Section: Introductionmentioning
confidence: 99%